Organisational Anatomy A Manager's Guide to a Healthy Organisation - Konovalov, Oleg (Towards the Twenty-First Century Organization, 2016)
This book offers a discussion of a new management concept, "Organisational Anatomy", which views organisational processes and functions from a biological perspective. This approach naturally explains the ongoing internal and external organisational processes and optimum configuration of different organisations. Organisations are live creatures which are breathing, functioning, moving and developing inside their specific environments. Biological examples offer a useful way of making sense of complex ideas, because they can be related to everyday existence. As such, this allows the reader to intuitively understand the organisations where they work and with which they interact.By classifying different types of organisations and looking at their biological functions, Organisational Anatomy links existing theories and discusses five archetypes of organisations, namely producers, knowledge-dependent, location-dependent, donor-dependent and state-affiliated organisations. By looking into their specific features, the characteristics of organisations of different ages and levels of maturity, the access and utilisation of resources, and the development of productive external relations, this book allows insights into the role of each function in achieving superior business performance. The Organisational Anatomy approach allows the development of a holistic picture, and will allow businesses to achieve higher performance and recognise problems and difficulties by considering organisational pathologies and diseases